REIMAGINING THE PAST: VERNACULAR GRAPHIC DESIGN OF GRAFIS NUSANTARA AND ITS EMOTIONAL IMPACT ON DIGITAL AUDIENCES - Kusuma Ayu, Intan; Ahmad Sofiyuddin Mohd Shuib; Nur Faizah Mohd Pahme (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2025)
This research analyzes the emotional impact of vernacular Indonesian graphic design from the 1960s–1990s, as archived by Grafis Nusantara, on Generation Z and Millennials. Using a netnographic approach, the research examines user interactions on Instagram and X (formerly Twitter), focusing on affective responses to vintage visuals. The results indicate that the use of dominant colors, hand-drawn illustrations, and decorative lettering play a key role on triggering shared nostalgic sentiment, evoking users to familial and cultural memories. This research asserts that emotional design significantly contributes in transforming cultural memory in the realm of digital media and provides meaningful contributions to the development of contemporary branding strategies using vernacular aesthetics.